Living Sunnah in Contemporary Character Education: A Thematic Study of the Prophet’s Hadith - Latifah, Aprina Noor; Hudaya, Hairul; Huda, Nuril (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Contemporary Islamic education faces serious challenges related to moral degradation, the weakening of social empathy, low self-control, and declining discipline among students, particularly in the context of globalization and digital culture. This article aims to analyze the values of character education contained in the hadith of the Prophet Muhammad through a thematic study using the perspective of living sunnah. This study employs a qualitative approach with library research, focusing on thematic (maudhu‘i) analysis of hadith related to character education. Primary data are drawn from selected prophetic hadiths and supported by secondary sources, including scholarly books and journal articles discussing living sunnah, character education, and contemporary educational issues. The data are analyzed by classifying the hadiths according to the main themes of character education and interpreting them within the framework of living sunnah. The findings indicate that the concept of living sunnah views hadith as living values that are internalized through the habituation of attitudes and behaviors. The thematic analysis reveals three core character values, such as social character and empathy, self-control, and manners and discipline, which are closely interconnected in shaping students’ moral integrity, emotional maturity, and sense of responsibility. The study concludes that character education based on living sunnah offers a relevant and contextual framework for addressing contemporary moral challenges by transforming prophetic teachings into lived ethical practices.